2014
DOI: 10.1111/ejn.12742
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the motor system to the perception of reachable space: an fMRI study

Abstract: The present functional magnetic resonance imaging (fMRI) study investigates the neural correlates of reachability judgements. In a block design experiment, 14 healthy participants judged whether a visual target presented at different distances in a virtual environment display was reachable or not with the right hand. In two control tasks, they judged the colour or the relative position of the visual target according to flankers. Contrasting the activations registered in the reachability judgement task and in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 79 publications
9
28
0
Order By: Relevance
“…These observations suggest that egocentric perspective might recruit motor representations to a greater extent than the allocentric perspective. Consistent with these arguments, it has also been shown that the perception of reachable versus unreachable objects activates fronto-parietal networks (i.e., the precuneus and the parieto-occipital junction, the anterior parts of the cingulate gyrus and superior and medial frontal gyri, bilaterally) and the cerebellum, suggesting a contribution of dynamic motor representations facilitating the perceptive discrimination of peri- and extrapersonal spaces ( Gallivan et al, 2009 ; Bartolo et al, 2014 ).…”
Section: Introductionmentioning
confidence: 60%
“…These observations suggest that egocentric perspective might recruit motor representations to a greater extent than the allocentric perspective. Consistent with these arguments, it has also been shown that the perception of reachable versus unreachable objects activates fronto-parietal networks (i.e., the precuneus and the parieto-occipital junction, the anterior parts of the cingulate gyrus and superior and medial frontal gyri, bilaterally) and the cerebellum, suggesting a contribution of dynamic motor representations facilitating the perceptive discrimination of peri- and extrapersonal spaces ( Gallivan et al, 2009 ; Bartolo et al, 2014 ).…”
Section: Introductionmentioning
confidence: 60%
“…Several studies have reported the same results (Valdès-Conroy et al 2012;Bartolo et al, 2014;Grade et al, 2015;Wamain et al, 2016), which could be due to participants experiencing difficulty responding around the more uncertain reachable space boundary.…”
Section: Reproduction Of Reachability Judgment Task Featuresmentioning
confidence: 68%
“…Behavioural as well as neuroimaging studies of the human neurotypical brain have provided evidence suggesting the specific processing of information in peripersonal and extrapersonal spaces. Object perception, in particular, seems to be associated with an activation of the motor system only when the object appears within the peripersonal space (Mark et al, 1997;Costantini et al, 2010;Iachini et al, 2014;Coello et al, 2008;Gallivan et al, 2009Gallivan et al, , 2011Bartolo et al, 2014). Thus, visual presentation of objects in peripersonal space has been found to activate not only occipital but also parietal, ventral and premotor cortices (Chao & Martin, 2000;Chao et al 2002;Creem-Regehr & Lee, 2005;Kan et al 2006;Martin, 2007), and sensori-motor cortices (Cardellicchio et al, 2011;Grafton et al, 1997;Matelli et al, 1985;Gallivan et al, 2011;Wamain et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…High-resolution anatomical images were collected with a T1-weighted magnetization-prepared rapid gradient multi-echo sequence (multi-echo MPRAGE [1], 176 sagittal slices, TR=2530 ms, TEs=1.69, 3.55, 5.41, and 7.27 ms, TI=1100 ms, flip angle=7°, 1 mm3 voxels, FOV=256 mm, GRAPPA acceleration=2). For functional runs, blood oxygenation level-dependent (BOLD) data were collected via a T2*-weighted echo-planar imaging (EPI) pulse sequence that employed multiband RF pulses and Simultaneous Multi-Slice (SMS) acquisition [2][3][4][5]. For the task runs, the EPI parameters were: 69 interleaved axial-oblique slices (25 degrees toward coronal from ACPC alignment), TR=1500 ms, TE=30 ms, flip angle=75°, 2.0 mm isotropic voxels, FOV=208 mm, in-plane acceleration factor (GRAPPA)=2, SMS factor=3).…”
Section: Supplementary Methodsmentioning
confidence: 99%